Complete versus culprit-only revascularization in patients with multi-vessel disease undergoing primary percutaneous coronary intervention: A meta-analysis of randomized trials. (1st May 2015) - Elgendy, Islam Y.; Huo, Tianyao; Mahmoud, Ahmed; Bavry, Anthony A.
Abstract: Background: The best approach for revascularization of multi-vessel coronary disease in patients with ST-elevation myocardial infarction (STEMI) undergoing primary percutaneous coronary intervention (PCI) is controversial. Methods: We searched the Medline and Web of Science databases, the Cochrane Register of Controlled Trials, and major conference proceedings for clinical trials that randomized STEMI patients with multi-vessel disease to a complete versus culprit-only revascularization strategy. Random effects summary risk ratios (RR) were constructed using a DerSimonian–Laird model. Results: A total of 6 trials met our selection criteria, which yielded 1, 190 patients. The mean follow-up duration was 20.5 months. The incidence of major adverse cardiac events was significantly reduced in the complete revascularization group versus the culprit-only revascularization group (RR 0.57, 95% confidence interval (CI) 0.41–0.78, p < 0.001). This was due to a lower risk of urgent revascularization with complete revascularization (RR 0.55, 95% CI 0.35–0.86, p = 0.01). A non-significant reduction was observed with complete versus culprit-only revascularization for the combined outcome of mortality or myocardial infarction (RR 0.56, 95% CI 0.30–1.04, p = 0.06). Conclusion: Complete revascularization of significant coronary lesions at the time of primary PCI in patients with STEMI and multi-vessel disease was associated with better outcomes. This was primarily due to a reduction in the need for urgent revascularization. Larger trials are needed to determine if complete revascularization reduces death or myocardial infarction.